Between the Tunebo and the U’wa: the place of the historical arguments in the discussio on rights of groupn - Uribe Botero, Ángela (Estudios de Filosofía, 2003)
The purpose of this article is to strengthen the links between reasons of justice and historical reasons in order to justify the recognition of certain rights for cultural groups I try to show that in the struggles to defend the preservation of some cultures it is not marginal, but rather essential, the fact that this defense arises from an exclusion history. Considering some examples, in the first part of the paper I intend to integrate some of the features that, from Charles Taylor’s point of view, constitute identity, to the stages that, according to Luis Villoro are involved in the projection of a model of justice. In the second part. I recount some episodes of the U’wa recent process of territorial recuperation in Colombia. The purpose of telling that story is to strengthen the relationship that, from Luis Villoro’s point of view, exists between exclusion stories and the consolidation processes of justice. As a conclusion, and taking account of Ernst Tugendhat’s difference between general and special rights. I will show to what extent sad stories are still contents for justice although the positive law has already recognized a series of rights.